11. KNOWLEDGE, PRACTICE OF STANDARD PRECAUTIONS OF NURSES AT VIETNAM NATIONAL EYE HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Purpose: Describe the current situation of knowledge and practice of standard precautions of nurses at the Vietnam National Eye Hospital in 2024.Methods: Cross-sectional study was conducted on 175 nurses is taking care of patients in clinical departments and clinic systems at the Vietnam National Eye HospitalResults: The overall average knowledge score was 41.51±5.74. The proportion of subjects with general knowledge about standard precautions reached 66.9% (117 nurses); 33.1% have inadequate knowledge (58 nurses). Percentage of nurses who practice hand washing or disinfecting hands with alcohol at the right time; Using correct protective equipment (masks, hats) reached the highest levels of 86.3% and 88.6%. The lowest rate of practicing nurses was in the content of intramuscular and intravenous injection practice (81.7% and 84.0%). The percentage of nurses with standard general prevention practices is 81.7%.Conclusion: Nurses' practice of standard precautions is quite good, however, there is still 1/3 of nurses who do not have adequate knowledge of standard precautions. It is necessary to continue to increase the correct knowledge of standard precautions for nurses.
Keywords: knowledge; practice of standard precautions; nurses